2021
DOI: 10.26717/bjstr.2021.36.005880
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Сapabilities of Dental Powders Based on Composiitons “Nanosilica Asil A-300 + Herbal \ Mineral Powders” in the Prevention or Delay of Caries and Dental Diseases

Abstract: Introduction and Substantiation of the TopicPrevention of dental diseases should become the main direction of development of modern dentistry. Dental Wear and CariesDental wear and caries are not necessarily a harmful acquisition of civilization. Teeth work at the forefront of life in extreme conditions, withstanding colossal changes in temperature, aggressive influences and pressures. In fact, they work in roughly the same conditions as abrasive cutting edges, car tires, shoe soles and other wear&tear parts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The Chuiko Institute of Surface Chemistry was among the first institutions in the world to create its own Laboratory of Biocompatible Materials. It developed some of the first photopolymer highly filled compositions for prosthetics and filling in the USSR and the world, documented in a number of articles, patents and dissertations [1][2][3]. Accordingly, the Ukrainian SSR and then Ukraine became the place for the first introduction of both innovative photopolymer dental pastes (Oxomat, Stomadent, Esta, etc.)…”
Section: Dental Problems: Can We Help Ourselves?mentioning
confidence: 99%
See 2 more Smart Citations
“…The Chuiko Institute of Surface Chemistry was among the first institutions in the world to create its own Laboratory of Biocompatible Materials. It developed some of the first photopolymer highly filled compositions for prosthetics and filling in the USSR and the world, documented in a number of articles, patents and dissertations [1][2][3]. Accordingly, the Ukrainian SSR and then Ukraine became the place for the first introduction of both innovative photopolymer dental pastes (Oxomat, Stomadent, Esta, etc.)…”
Section: Dental Problems: Can We Help Ourselves?mentioning
confidence: 99%
“…Our experience has shown that this is possible when using ordinary available epoxy resins. The prospects for self-restoration with epoxy materials were described in general terms for the first time in our first publications [1][2][3], and above all in this publication [4].…”
Section: Dental Problems: Can We Help Ourselves?mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, in our opinion, the main direction in the development of dentistry of the future should be the prevention of dental diseases, and their treatment with minimal surgical intervention. We already have a positive experience in creating therapeutic prophylactic powders for damaged teeth [4][5]. However, work on the creation of epoxy composites for fillings represents a new special cycle, which has no analogues in the scientific literature so far.…”
Section: The Chuiko Institute Of Surface Chemistry Of the Nationalmentioning
confidence: 99%
“…Our Chuiko Institute of Surface Chemistry developed first in USSR/world acrylic photopolymer compositions for prosthetics and filling [1][2][3]. We already have a positive experience in creating prophylactic powders for damaged teeth [4]. Now, work on the creation of epoxycomposites for dental-fillings represents a new special cycle, which has no analogues in the world dental science.…”
Section: Introductionmentioning
confidence: 99%